Efektivitas Pelatihan Regulasi Emosi Untuk Meningkatkan Resiliensi Caregiver-keluarga Pasien Skizofrenia - R.A Diana Rahmi Andriani; Tina Afiatin; Rr Indahria Sulistyarini (JIP (Jurnal Intervensi Psikologi), 2017)
The study examined the effectiveness of emotion regulation training to improve schizophrenia familycaregiver’s resilience. This study usepre-post test control group design. The intervention consist 3 class sessions for two weeks and the duration of every session runs between 150- 180 minutes each. The participants were 10 schizophrenia caregivers from two desa in Moyudan Sleman. They were men and women aged between 39-57 years old, and classified into two groups. One group (n=5) received emotion regulation training as experimental group and the other (n=5) as controlled group (waiting list). Participant were assed using Connor-Davidson Resilience Scale (CD-RISC) before intervention (pre-tes,) after intervention (post-test,) and two weeks after intervention (follow-up). T-test analysis toward the gained score shows difference between the experimental group and controlled group. The experimental group shows significant improvement while the control group show less obvious improvement. The result concluded that emotion regulation training was significantly effective to improve resilience of schizophrenia familycaregiver.Key word: resilience, emotion regulation, schizophrenia family caregiver